Esculetin Alleviates Inflammation, Oxidative Stress and Apoptosis in Intestinal Ischemia/Reperfusion Injury via Targeting SIRT3/AMPK/mTOR Signaling and Regulating Autophagy - Shen X; Shi H; Chen X; Han J; Liu H; Yang J; Shi Y; Ma J (Dove Medical Press, 2023)
Xin Shen,1,* Hai Shi,1,* Xinli Chen,1 Junwei Han,1 Haiwang Liu,1 Jie Yang,1 Yuan Shi,2 Jiajia Ma2 1Department of Gastrointestinal Surgery, Xi'an Daxing Hospital, Xi'an, 710016, People's Republic of China; 2Department of Gynecology and Obstetrics, Xijing Hospital, Air Force Military Medical University, Xi'an, 710032, People's Republic of China*These authors contributed equally to this workCorrespondence: Jiajia Ma, Xijing Hospital, Air Force Military Medical University, No. 15 Changle Western Road, Xincheng District, Xi'an, Shaanxi, 710032, People's Republic of China, Email majiajia69_11122@163.comAim: Intestinal ischemia/reperfusion (I/R) injury is a challenging pathological phenomenon accountable for significant mortality in clinical scenarios. Substantial evidence has supported the protective role of esculetin in myocardial I/R injury. This study is designed to reveal the specific impacts of esculetin on intestinal I/R injury and disclose the underlying mechanism.Methods: First, intestinal I/R injury model and intestinal epithelial cell line hypoxia/reoxygenation (H/R) model were established. Pathologic damages to intestinal tissues were observed through H&E staining. Serum diamine oxidase (DAO) levels were examined. RT-qPCR and Western blot examined the expression of inflammatory mediators. Commercial kits were used for detecting the levels of oxidative stress markers. TUNEL assay and caspase 3 activity assay measured cell apoptosis. Immunofluorescence (IF) staining measured autophagy levels. Western blot analyzed the expression of apoptosis-, Sirtuin 3 (SIRT3)/AMP activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling- and autophagy-related proteins. Molecular docking verified the interaction of esculetin with SIRT3. Cell viability was explored via CCK-8 assay.Results: The experimental results revealed that esculetin treatment mitigated pathological damage of intestinal tissues, reduced serum DAO level, ameliorated inflammation, oxidative stress and apoptosis and promoted autophagy in intestinal I/R rats. Moreover, esculetin bond to SIRT3 and activated SIRT3/AMPK/mTOR signaling both in vitro and in vivo. Furthermore, esculetin treatment enhanced cell viability and SIRT3 silencing reversed the impacts of esculetin on autophagy, inflammation, oxidative stress and apoptosis in H/R cell model.Conclusion: In a word, esculetin activated SIRT3/AMPK/mTOR signaling and autophagy to protect against inflammation, oxidative stress and apoptosis in intestinal I/R injury.Keywords: intestinal I/R injury, autophagy, esculetin, SIRT3/AMPK/mTOR signaling